Self-healing in-situ ceramization flame-retardant silicone rubber and preparation method thereof

CN122978713APending Publication Date: 2026-10-27STATE GRID JIANGSU ELECTRIC POWER CO LTD RESEARCH INSTITUTE +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611468061.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

Smart Images

  • Figure CN122978713A_ABST
    Figure CN122978713A_ABST
Patent Text Reader

Abstract

The application discloses a self-healing in-situ ceramization flame-retardant silicone rubber and a preparation method thereof, and belongs to the field of fireproof flame-retardant and functional polymer materials. The preparation method comprises the following steps: uniformly mixing hydroxyl-terminated siloxane and a crosslinking agent containing a borate ester bond at room temperature under low-speed stirring to obtain a regulated self-healing matrix precursor with a dynamic covalent network; after vacuum drying of a ceramization precursor and a flame-retardant filler, the regulated self-healing matrix precursor is added in sequence, and uniform mixing is performed under accelerated stirring; in the third step, a catalyst is added and uniformly mixed, and after casting a mold, room temperature curing is performed to obtain the self-healing in-situ ceramization flame-retardant silicone rubber. The self-healing in-situ ceramization flame-retardant silicone rubber provided by the application realizes performance synergistic improvement of flame retardation, fire prevention, high mechanical strength and self-healing capability, has the dual functions of "self-repairing in normal times and anti-ablation in disaster times", and is suitable for fire-resistant sealing of key parts such as cable penetration holes, tunnels and pipe corridors and energy storage power stations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fireproof and flame-retardant functional polymer materials, specifically relating to a self-healing in-situ ceramicized flame-retardant silicone rubber and its preparation method. Background Technology

[0002] Flame-retardant and fire-resistant materials are a key component in ensuring fire safety in construction, power, and transportation sectors, and are widely used for sealing and fireproofing cable penetrations, tunnels, and energy storage power stations. Silicone rubber, due to its excellent resistance to high and low temperatures, flexibility, and insulation properties, is considered one of the ideal matrix materials. However, traditional silicone rubber-based fire-stopping materials have several inherent defects, making it difficult to meet the increasingly stringent safety and durability requirements.

[0003] First, because the cross-linked network of traditional silicone rubber materials consists of permanent covalent bonds, these bonds break after mechanical damage or long-term stress deformation, rendering the material unable to repair itself. The irreversible accumulation of cracks and damage significantly reduces the effectiveness and lifespan of the fire-resistant seal of traditional silicone rubber materials, necessitating frequent maintenance or replacement, increasing operating costs and safety risks. Second, and more critically, its performance in a fire presents a bottleneck. While some flame-retardant silicone rubbers or those with added intumescent flame retardants (such as ammonium polyphosphate) can expand into charcoal upon exposure to fire, forming a heat-insulating layer, this char layer has low strength and poor toughness, making it prone to collapse and pulverization under flame impact or mechanical disturbance. This leads to the failure of the fire-resistant seal barrier, creating new channels for flame and smoke spread. The fundamental reason for this is that traditional silicone rubber materials lack a rigid framework to maintain structural integrity at high temperatures.

[0004] For example, invention patent CN115537137B discloses a ceramizable silicone rubber composite, ceramizable silicone rubber, its preparation method, and its uses. The ceramizable silicone rubber composite has at least three layers: an adhesive layer, a heat-insulating layer, and a flame-retardant layer. The raw materials for the flame-retardant layer include: raw silicone rubber, a structure control agent, reinforcing filler, a flame retardant, a ceramic-forming filler, low-melting-point inorganic materials, reinforcing fibers, and a vulcanizing agent. The silicone rubber is selected from at least one of methyl vinyl silicone rubber raw material and methyl silicone rubber raw material. The vulcanizing agent is selected from compounds containing a peroxide structure. The ceramizable silicone rubber composite obtained by this invention exhibits significantly improved mechanical properties before ceramic formation, thermal stability, and ceramic-forming performance under fire conditions, demonstrating high overall performance. For example, invention patent CN103613934B discloses a fire-resistant silicone rubber self-adhesive tape and its preparation method. This self-adhesive tape is mainly composed of the following components and parts by weight: 100 parts methyl vinyl silicone rubber, 15-40 parts silica, 5-20 parts alumina, 1-4 parts structure control agent, 1.5-3 parts sintering additive, 0.15-1 part surface treatment agent, 0.5-2 parts crosslinking agent, 0.5-1 part polytetrafluoroethylene ultrafine powder, 0.5-2 parts borate ester, and 0.5-2 parts tackifying resin. The crosslinking agent is dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, or 2,4-dichlorobenzoyl peroxide. This invention enables the silicone rubber to form a ceramic protective layer. Its ceramic structure is stable, has strong adhesion, high hardness, is not easily detached, and has good density, making it difficult to form channels, thus playing a role in flame isolation. It can be widely used in the processing of wire and cable repair and connection. However, the aforementioned literature uses peroxide-based vulcanizing agents or crosslinking agents to permanently vulcanize and crosslink silicone rubber, which provides silicone rubber with many advantages in terms of stability and flame retardancy. However, none of these methods can provide silicone rubber with self-healing properties, resulting in insufficient damage resistance and limited service life of silicone rubber during long-term daily use.

[0005] Therefore, it is urgent to develop a new type of fire-stopping material that can overcome the above limitations, which can self-repair damage and extend service life at room temperature; and can quickly transform into a robust fire-resistant protective layer in high-temperature fire environments, providing a durable and stable fire barrier for the underlying structure. Summary of the Invention

[0006] To address the aforementioned technical challenges, this invention innovatively integrates dynamic covalent chemistry and ceramicization technology to provide a self-healing in-situ ceramicized flame-retardant silicone rubber and its preparation method. This rubber possesses the dual functions of "self-repair in normal conditions and ablation resistance in disasters": it can autonomously repair damage and extend its service life at room temperature; and in high-temperature fire environments, it can rapidly transform into a robust ceramic protective layer, providing a durable and stable fire-resistant barrier for the underlying structure.

[0007] In a first aspect, the present invention provides a method for preparing self-healing in-situ ceramicized flame-retardant silicone rubber, comprising the following steps: Step 1: Mix terminal hydroxyl siloxane and boron ester crosslinking agent at low speed at room temperature to obtain a self-healing matrix precursor with dynamic covalent network. Step 2: After vacuum drying the ceramicized precursor and flame-retardant filler, add the self-healing matrix precursor in sequence and accelerate stirring to mix evenly. Step 3: Add catalyst and mix evenly, then pour into mold and cure at room temperature to obtain the self-healing in-situ ceramicized flame-retardant silicone rubber; The ceramicized precursor includes a premixed silicon-containing component, low-temperature glass powder, and metal oxides. The silicon-containing component includes one or more of nano-silica, silica powder, and silica sol. The softening point of the low-temperature glass powder is between 400 ℃ and 600 ℃, and includes one or more of borosilicate glass powder and phosphate glass powder; The metal oxide includes one or more of kaolin, mica powder, aluminum hydroxide, and aluminum oxide.

[0008] To better integrate the dynamic covalent chemistry technology and the ceramicization technology of silicone rubber, this invention has conducted in-depth research and screening of process steps and conditions. First, a dynamic covalent network is formed by low-speed stirring at room temperature, effectively avoiding the destruction of newly formed borate ester bonds by high shear forces, thus ensuring the integrity of the network in the self-healing matrix precursor. Next, the vacuum-dried ceramicization precursor and flame-retardant filler are uniformly dispersed in a low-viscosity matrix under accelerated stirring, preventing material agglomeration and laying the foundation for the subsequent formation of a continuous and dense ceramic layer. Appropriate materials are pre-mixed in the ceramicization precursor to form a dense ceramic layer without penetrating cracks at high temperatures. Then, a catalyst is added and the stirring speed is controlled to ensure uniform catalyst dispersion while preventing premature over-crosslinking, ensuring smooth casting and thus obtaining a high-quality, uniformly produced, in-situ ceramicized flame-retardant silicone rubber.

[0009] In the ceramic precursor, the silicon-containing component can provide a highly active silicon source. Low-temperature glass powder (softening point 400-600℃) melts and flows first to fill the pores at fire temperature. Metal oxides (kaolin, mica powder, etc.) provide elements such as Al and K to participate in the formation of a high-melting-point ceramic phase. The three together realize the gradient transformation process of low-temperature melting and filling and high-temperature ceramicization, so that the ceramic layer gradually becomes denser from the outside to the inside, avoiding through cracks caused by thermal expansion mismatch.

[0010] Furthermore, the hydroxyl-terminated siloxanes include α,ω-dihydroxy polydimethylsiloxane, whose number-average molecular weight Mn is 10,000-100,000; Borate ester crosslinking agents include one or more of triethyl borate, tri-n-propyl borate, triisopropyl borate, and bisphenol A borate. The catalysts include silane coupling agents and dibutyltin dilaurate.

[0011] This invention controls the number-average molecular weight of terminal hydroxyl siloxanes to 10,000-100,000, ensuring sufficient flexibility and mechanical strength in the matrix, while also facilitating the optimization of the balance between self-healing efficiency and processing rheological properties. Furthermore, the boron ester crosslinking agent not only acts as a dynamic crosslinking agent to construct a self-healing network, but the boron element in its molecular structure also serves as a ceramicization conversion aid, promoting the formation of continuous and dense BO-Si and BO-Al chemical bonds in the ceramicization precursor at high temperatures, thereby constructing a composite ceramic framework.

[0012] Furthermore, the flame-retardant filler includes premixed inorganic hydroxides, expandable carbon sources, and carbonization catalysts; In step two, the ceramicized precursor and flame-retardant filler are vacuum dried in a vacuum oven at 60-80℃ for 10-15 hours.

[0013] The inorganic hydroxides (preferably hydrophobically modified) in the flame-retardant filler decompose and absorb heat at high temperatures, releasing water vapor. The expandable char source (preferably grafted modified) forms an expandable char layer, and the char-forming catalyst promotes the densification of the char layer. Together, these three components can achieve multiple flame-retardant mechanisms such as cooling, oxygen isolation, and smoke suppression, thereby improving the flame-retardant properties of silicone rubber while providing strength.

[0014] Furthermore, the preparation method further includes adding reinforcing fibers in at least one of (1) and (2): (1) In step two, the reinforcing fiber pretreatment is added to the self-healing matrix precursor after the flame retardant filler is added; (2) In step one, the reinforcing fiber is pretreated, premixed with terminal hydroxyl siloxane, and then mixed with a boron ester crosslinking agent so that the reinforcing fiber is pre-embedded in the dynamic covalent network; The pretreatment of the reinforcing fibers includes: Keep the reinforcing fibers at 350-400℃ for 30-60 minutes; The reinforcing fibers are surface activated using plasma or corona treatment.

[0015] The reinforcing fibers are heat-treated at 350-400℃ to remove the surface organic coating and form an active silanol surface. The second method is preferred for adding the reinforcing fibers, which involves dispersing the pretreated reinforcing fibers in the terminal hydroxyl siloxane for premixing, and then mixing them with a borate ester crosslinking agent at low speed at room temperature. The reinforcing fibers and terminal hydroxyl siloxane are mixed using a low-viscosity premixing process: the pretreated reinforcing fibers are first added to the terminal hydroxyl siloxane and premixed at low speed at room temperature to allow the reinforcing fibers to be fully dispersed as monofilaments in the low-viscosity system; after the reinforcing fibers are uniformly dispersed, the borate ester crosslinking agent is added for mixing, so that the uniformly dispersed reinforcing fibers are anchored by hydrogen bonds / chemical bonds with the borate ester bonds and / or terminal hydroxyl siloxane segments in the dynamic covalent network through their surface active hydroxyl groups, thereby pre-embedding them in the dynamic covalent network, avoiding the aggregation of reinforcing fibers in the matrix, and also helping to improve the overall impact toughness and structural integrity, and preventing the ceramic layer from cracking and pulverizing at high temperatures.

[0016] Furthermore, in step one, stir at a first stirring speed of 20-50 rpm for 8-15 minutes; In step two, stir at the second stirring speed of 100-200 rpm for 45-75 minutes; In step three, in-situ reactive stirring is carried out at a gradually decreasing third stirring speed, including the following steps: V1 is 120-150 rpm, stirring for 1-3 min, to rapidly and uniformly disperse the catalyst in a low-viscosity system under high-speed shear; V2 is 80-110 rpm, stirring for 1-3 minutes. Under medium-speed shear, the materials are fully in contact and reacted. The heat generated by stirring and shear is controlled to keep the system temperature below 35℃. V3 is stirred at 40-70 rpm for 0.5-2 min to allow air bubbles to escape from the system under low-speed shearing and to prevent excessive cross-linking.

[0017] The control of stirring speed in each step of this invention is crucial. The process progresses from low-speed stirring in step one to accelerated stirring in step two, and finally to a segmented variable-speed stirring process in step three, characterized by high-speed, medium-speed, and low-speed stirring. In step three, with a total stirring time not exceeding 8 minutes and the system temperature consistently below 35°C, the high-speed stage ensures rapid and uniform macroscopic dispersion of the catalyst; the medium-speed stage controls shear heat generation to prevent localized overheating and premature cross-linking; and the low-speed stage allows microbubbles to escape and prevents excessive cross-linking that could lead to a sudden increase in viscosity. This ensures optimal fluidity and uniformity of the system before casting, significantly improving the consistency of the mechanical properties and self-healing efficiency of the cured material.

[0018] Secondly, the present invention also provides a self-healing in-situ ceramicized flame-retardant silicone rubber prepared by the above preparation method, wherein, by weight, its raw material composition includes: Adjust the amount of self-healing matrix precursor to 25-55 parts; 25-40 parts of ceramization precursor; 20-35 parts of flame-retardant filler; Catalyst 1.0-2.5 parts; In the self-healing matrix precursor, the mass ratio of terminal hydroxyl siloxane to boron ester crosslinking agent is (5-15):1; The ceramic precursor comprises a silicon component provider, low-temperature glass powder, and metal oxide in a mass ratio of (3-6):(4-8):(2-5).

[0019] Furthermore, the flame-retardant filler includes an inorganic hydroxide, an expandable carbon source, and a carbonization catalyst in a mass ratio of (4-8):(1-3):(1-3); The catalyst comprises a silane coupling agent and dibutyltin dilaurate (DBTDL) in a mass ratio of (5-12):(4-8).

[0020] Furthermore, by weight, the raw material composition of the self-healing in-situ ceramicized flame-retardant silicone rubber includes: Add 30-45 parts of the self-healing matrix precursor; 30-35 parts of ceramicized precursor; 25-30 parts of flame-retardant filler; 1.2-2.0 parts of catalyst.

[0021] Furthermore, in the ceramicized precursor, the mass ratio of the silicon component provider, the low-temperature glass powder, and the metal oxide is 5:6:4.

[0022] Furthermore, in the flame-retardant filler, the mass ratio of the inorganic hydroxide, the expanded carbon source, and the carbon-forming catalyst is 5:2:2.

[0023] This invention achieves a four-fold composite function of self-healing, ceramization, flame retardancy, and reinforcement through optimized component ratios. Controlling the dynamic cross-linking density of the self-healing matrix precursor ensures sufficient self-healing efficiency; the ceramization precursor forms a sufficient ceramic framework at high temperatures; the flame-retardant filler achieves efficient flame retardancy and smoke suppression; and the catalyst ensures the curing reaction proceeds fully.

[0024] Furthermore, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (KH-550) and γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560).

[0025] Furthermore, it also includes 2.5-5.0 parts of reinforcing fiber, wherein the reinforcing fiber is chopped fiber with a length of 1-6 mm and a diameter of 5-20 μm, and is selected from one or more of basalt fiber, glass fiber, and aluminosilicate ceramic fiber.

[0026] This invention selects short-cut fibers, which not only ensures the uniform dispersion of fibers in a low-viscosity matrix (too long fibers are prone to entanglement, while too short fibers have insufficient reinforcement effect), but also selects basalt fibers, glass fibers and / or aluminosilicate ceramic fibers to react with ceramic precursors at high temperatures to form a fiber-ceramic composite structure, which significantly improves the flexural strength and impact resistance of the ceramic layer.

[0027] Furthermore, in the flame-retardant filler, the inorganic hydroxide is one or a combination of two of aluminum hydroxide and magnesium hydroxide, and the surface of the inorganic hydroxide is hydrophobically modified by a silane coupling agent or hexamethyldisilazane. The expandable carbon source is one or a combination of two of expanded graphite and expandable graphite, and the surface of the expandable carbon source is grafted and modified with a silane coupling agent. The char-forming catalyst is one or more of ammonium polyphosphate, melamine phosphate, and pentaerythritol phosphate.

[0028] After hydrophobic modification, the dispersibility of inorganic hydroxides in the matrix is ​​significantly improved, avoiding agglomeration that leads to localized flame retardant failure. Grafting modification of the expandable char source enhances its interfacial bonding with the matrix, allowing for controllable expansion ratio and uniformity. The char-forming catalyst (ammonium polyphosphate, etc.) catalyzes the formation of a dense char layer at high temperatures. The combination of these three elements achieves a three-step flame retardant mechanism of cooling, expansion, and char formation, significantly reducing heat release and smoke production.

[0029] Furthermore, the self-healing in-situ ceramicized flame-retardant silicone rubber exhibits a tensile strength exceeding 18 MPa and a flexural strength exceeding 15 MPa, with both tensile and flexural strength gradually increasing from 400°C to 800°C. The self-healing in-situ ceramicized flame-retardant silicone rubber provided by this invention differs from traditional ceramicized materials in that their strength drops sharply at high temperatures. It achieves continuous enhancement of "anti-ablation resistance during disasters," providing a durable and stable fire-resistant barrier for critical components such as cable penetrations, tunnel corridors, and energy storage power stations, and has significant potential for widespread application. The self-healing in-situ ceramicized flame-retardant silicone rubber and its preparation method provided by this invention have at least the following beneficial effects: 1. This invention integrates dynamic covalent chemistry and ceramicization techniques to construct a dynamic covalent network of borate esters within a silicone rubber matrix. This enables the silicone rubber to exhibit excellent self-healing capabilities at room temperature (self-healing efficiency exceeding 92% in multiple embodiments), allowing it to autonomously repair mechanical damage and cracks, significantly extending material lifespan and reducing maintenance costs. Simultaneously, the material can transform in situ into a high-strength ceramic layer under high-temperature fire conditions (e.g., 400-800℃), with tensile strength exceeding 18MPa and flexural strength exceeding 15MPa. Furthermore, the tensile and flexural strengths gradually increase from 400℃ to 800℃, demonstrating the significant characteristics and advantages of gradient ceramicization reinforcement. This addresses industry pain points such as the difficulty of flame retardancy and fire prevention in the insulation protection of flexible organic materials for electrical equipment, and the sharp drop in strength of traditional ceramicized materials at high temperatures, achieving a dual function of "self-repair in normal times and resistance to ablation in disasters."

[0030] 2. This invention constructs a triple fire protection mechanism of flame retardancy, smoke suppression, and ceramicization through the synergistic effect of ceramicized precursors, flame-retardant fillers, and dynamic borosilicate ester networks: Flame-retardant fillers (aluminum hydroxide, expanded graphite, ammonium polyphosphate, etc.) achieve rapid flame retardancy and smoke suppression in the early stage of a fire by decomposing and absorbing heat, expanding into char, and catalytically forming char, resulting in a higher loss on ignition (LOI) and a decrease in total heat release and total smoke production; As the temperature rises, ceramicized precursors (silica sol, borosilicate glass powder, kaolin, etc.) form a composite ceramic skeleton containing BO-Si and BO-Al chemical bonds under the promotion of boron in the dynamic borosilicate ester network, making the ceramic layer dense and free of penetrating cracks, effectively blocking the spread of flames and smoke, and achieving a continuous transition from flame retardancy and smoke suppression to ceramicized refractory.

[0031] 3. This invention, through formula optimization and process innovation, overcomes the technical bottleneck of traditional silicone rubber in achieving a balance between mechanical properties, flame retardant properties, and self-healing properties. While ensuring self-healing performance, it achieves excellent mechanical properties, with strength gradually increasing from 400℃ to 800℃, overcoming the defect of traditional silicone rubber's rapid decline in mechanical properties at high temperatures. Furthermore, the preparation method of this invention employs a combination of room temperature low-speed stirring and segmented variable-speed stirring, resulting in mild process conditions, simple operation, and ease of large-scale production. This provides a novel comprehensive solution with both self-healing and ablation-resistant functions for fire-resistant sealing of critical components such as cable penetrations, tunnel corridors, and energy storage power stations. Attached Figure Description

[0032] Figure 1 The graph shows the self-healing efficiency of the silicone rubbers obtained in Examples 1-6 and Comparative Examples 2-3. Figure 2 SEM images of the charcoal slag in Comparative Examples 1-3 are shown, with Comparative Example 1 corresponding to (a), Comparative Example 2 corresponding to (b), and Comparative Example 3 corresponding to (c). Figure 3The images are SEM images of the charcoal slag from Examples 1-3, where Example 1 corresponds to (a), Example 2 corresponds to (b), and Example 3 corresponds to (c). Detailed Implementation

[0033] To better understand the above technical solutions, a detailed description of the solutions will be provided below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0034] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, and “multiple” generally includes at least two unless the context clearly indicates otherwise.

[0035] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such an article or device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device that includes said element.

[0036] This invention provides a self-healing in-situ ceramicized flame-retardant silicone rubber and its preparation method. The raw material composition of the self-healing in-situ ceramicized flame-retardant silicone rubber, by weight, includes: (1) 25-55 parts, preferably 30-45 parts, of a self-healing matrix precursor comprising a hydroxyl-terminated siloxane and a borate ester crosslinking agent in a mass ratio of (5-15):1, wherein the hydroxyl-terminated siloxane and the borate ester crosslinking agent are mixed uniformly at low speed and room temperature to obtain the self-healing matrix precursor with a dynamic covalent network; wherein: Hydroxyl-terminated siloxanes include α,ω-dihydroxy polydimethylsiloxane, whose number-average molecular weight Mn is 10,000-100,000; Borate ester crosslinking agents include one or more of triethyl borate, tri-n-propyl borate, triisopropyl borate, and bisphenol A borate.

[0037] (2) 25-40 parts, preferably 30-35 parts, of a ceramicization precursor, comprising a silicon component provider, low-temperature glass powder, and metal oxide in a mass ratio of (3-6):(4-8):(2-5); wherein: Silicon-containing components include one or more of nano-silica, silica powder, and silica sol; The softening point of low-temperature glass powder is between 400 ℃ and 600 ℃, including one or more of borosilicate glass powder and phosphate glass powder; Metal oxides include one or more of the following: kaolin (Al2[(OH)4 / Si2O5]), mica powder (SiO2 / Al2O3), aluminum hydroxide, and aluminum oxide.

[0038] (3) 20-35 parts of flame-retardant filler, preferably 25-30 parts, comprising an inorganic hydroxide, an expandable carbon source, and a carbon-forming catalyst in a mass ratio of (4-8):(1-3):(1-3); wherein: The inorganic hydroxide is one or a combination of two of aluminum hydroxide and magnesium hydroxide, and the surface of the inorganic hydroxide is modified by hydrophobication with a silane coupling agent or hexamethyldisilazane. The expandable carbon source is one or a combination of two of expanded graphite and expandable graphite, and the surface of the expandable carbon source is grafted and modified with a silane coupling agent. The char-forming catalyst is one or more of ammonium polyphosphate, melamine phosphate, and pentaerythritol phosphate.

[0039] (4) 1.0-2.5 parts of catalyst, preferably 1.2-2.0 parts, comprising a silane coupling agent and dibutyltin dilaurate (DBTDL) in a mass ratio of (5-12):(4-8), wherein the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (KH-550) and γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560).

[0040] Optionally, (5) 2.5-5.0 parts of reinforcing fiber, preferably 3-3.5 parts, wherein the reinforcing fiber is a short-cut fiber with a length of 1-6 mm and a diameter of 5-20 μm, selected from one or more of basalt fiber, glass fiber, and aluminosilicate ceramic fiber.

[0041] To obtain the self-healing in-situ ceramicized flame-retardant silicone rubber, the present invention also provides a corresponding preparation method, including the following steps: Step 1: Mix the terminal hydroxyl siloxane and the borate ester crosslinking agent at room temperature with a first stirring speed of 20-50 rpm for 8-15 minutes to obtain a self-healing matrix precursor with a dynamic covalent network. In a preferred embodiment, the pretreated reinforcing fibers are pre-dispersed in the terminal hydroxyl siloxane, and then mixed uniformly with a borate ester crosslinking agent at low speed and room temperature. The reinforcing fibers and terminal hydroxyl siloxane employ a low-viscosity pre-dispersion process: the pretreated reinforcing fibers are first added to the terminal hydroxyl siloxane and pre-mixed at low speed and room temperature to ensure sufficient monofilament dispersion of the reinforcing fibers in the low-viscosity system; after uniform dispersion of the reinforcing fibers, the borate ester crosslinking agent is added and mixed, allowing the uniformly dispersed reinforcing fibers to form hydrogen bonds / chemical bonds with the borate ester bonds and / or terminal hydroxyl siloxane segments in the dynamic covalent network through their surface-active hydroxyl groups, thereby uniformly pre-embedding the monofilament reinforcing fibers into the dynamic covalent network.

[0042] Step 2: Dry the ceramicized precursor and flame-retardant filler in a vacuum oven at 60-80℃ for 10-15 hours. Then add the self-healing matrix precursor in sequence and stir at the second stirring speed of 100-200 rpm for 45-75 minutes until the mixture is uniform. Step 3: Add catalyst and mix evenly. After casting into a mold, cure at room temperature to obtain the self-healing in-situ ceramic flame-retardant silicone rubber.

[0043] In step three of a preferred embodiment, after adding the catalyst, in-situ reactive stirring is performed at a gradually decreasing third stirring speed, comprising the following steps: V1 is 120-150 rpm, stirring for 1-3 min, to rapidly and uniformly disperse the catalyst in a low-viscosity system under high-speed shear; V2 is 80-110 rpm, stirring for 1-3 min. Under medium-speed shear, the catalyst is fully contacted and reacted with the active sites. The heat generated by stirring and shear is controlled to keep the system temperature below 35℃, preferably below 30℃, to avoid local overheating and premature cross-linking. V3 is set to 40-70 rpm, and stirred for 0.5-2 minutes. The low-speed shearing allows the bubbles in the system to escape and the condensation reaction that has been initially triggered to proceed smoothly under mild conditions, preventing excessive cross-linking that would cause a sudden increase in the viscosity of the system and make it impossible to cast.

[0044] In step three, the segmented variable speed stirring is used, with a total duration of no more than 8 minutes, and the system temperature is preferably kept below 35°C throughout the stirring process.

[0045] The sources of some of the raw materials and reagents used in the following examples, comparative examples, and tests are shown in Table 1: Table 1

[0046] The pretreatment of basalt fibers includes: removing the organic coating by holding at 375℃ for 45 minutes, followed by surface activation treatment of the fibers using oxygen plasma. Aluminum hydroxide and expanded graphite are pre-treated with silane coupling agents.

[0047] Example 1 This embodiment provides a self-healing in-situ ceramicized flame-retardant silicone rubber, the preparation method of which is shown below: Step 1: Add 27.3g of α,ω-dihydroxypolydimethylsiloxane (PDMS) and 2.7g of triethyl borate to a dual planetary mixer at room temperature and mix at a low speed of 30rpm for 10 minutes to initially disperse and form a self-healing matrix precursor. Step 2: After drying, add the ceramicized precursor (10g silica sol, 12g borosilicate glass powder, 8g kaolin), flame retardant filler (15g aluminum hydroxide, 6g expanded graphite, 6g ammonium polyphosphate), and 3g basalt fiber to the above self-healing matrix precursor and stir at 150 rpm for 60 minutes.

[0048] Step 3: Add a catalyst containing 0.64g of γ-aminopropyltriethoxysilane (KH-550) and 0.56g of dibutyltin dilaurate (DBTDL), and stir in situ at 120rpm for 8 minutes to obtain a homogeneous mixture. Then, cast the homogeneous mixture into a mold and cure at room temperature to obtain a self-healing, in-situ ceramizable, fire-retardant silicone rubber.

[0049] Example 2-3 The only difference between Examples 2 and 3 and Example 1 is the mass ratio of the self-healing matrix precursor, ceramicized precursor, flame-retardant filler, reinforcing fiber and catalyst. The proportions of each substance in this example are shown in Table 2.

[0050] Example 4 The difference between Example 4 and Example 2 is that no reinforcing fibers are used.

[0051] Example 5 The difference between Example 5 and Example 2 lies in the method of adding the reinforcing fibers. In step one of Example 4, 3g of basalt fiber was first premixed with α,ω-dihydroxypolydimethylsiloxane (PDMS), uniformly mixed under low-temperature and low-speed stirring, and then mixed with triethyl borate to form a self-healing matrix precursor. The remaining steps were the same as in Example 2.

[0052] Example 6 The difference between Example 6 and Example 5 is that in step three of Example 5, after adding the catalyst, in-situ reactive stirring with a gradually decreasing stirring speed is used, which includes the following steps: V1 is 150 rpm, stirring for 2 min, to rapidly and uniformly disperse the catalyst in a low viscosity system under high-speed shear; V2 is 100 rpm, and the stirring is carried out for 2 min. Under medium-speed shear, the catalyst is fully contacted and reacted with the active sites. The heat generated by stirring and shear is controlled to keep the system temperature at about 30℃ to avoid local overheating and premature cross-linking. V3 is stirred at 60 rpm for 2 minutes to allow the bubbles in the system to escape fully under low-speed shearing.

[0053] Comparative Example 1 Comparative Example 1 is a commercially available silicone rubber whose main components are α,ω-dihydroxypolydimethylsiloxane (PDMS) and silazane.

[0054] Comparative Examples 2-3 The only difference between Comparative Examples 2 and 3 and Example 1 is the mass ratio of the self-healing matrix precursor, ceramicized precursor, flame-retardant filler, reinforcing fiber, and catalyst. The proportions of each substance in this example are shown in Table 2.

[0055] Table 2 Content of various substances in different flame-retardant silicone rubbers

[0056] Performance testing and results:

[0057] 1: Combustion, cone calorimetry, and oxygen index tests

[0058] 1) Combustion test Combustion performance was tested in a fume hood using the vertical combustion method (UL-94), according to ASTM D3801. Combustion phenomena were observed, and the self-extinguishing time of the samples after removal of the flame was recorded using a stopwatch.

[0059] 2) Cone calorimetry test A Tech-GBT16172 cone calorimeter was used, with an operating voltage of 230V, a power of 5000W, and a heat output of 0-120kW / m³. 2 The main working principle of a cone calorimeter is the oxygen consumption principle. When a sample burns under the thermal radiation of a cone-shaped electric heater, the flame consumes a certain concentration of oxygen in the air and releases a certain amount of calorific value. A cone calorimeter can be used to measure parameters such as the heat release rate / total amount, the flue gas release rate / total amount, and the rate of generation of toxic gas CO, which can be used to assess the fire hazard of materials.

[0060] 3) Oxygen Index Test The oxygen index test involves vertically fixing a sample in a transparent glass combustion chamber filled with an upward-flowing mixture of oxygen and nitrogen gas, igniting the top of the sample, and observing its combustion characteristics to estimate the minimum oxygen concentration required to sustain combustion of the material. The plate dimensions are 100 × 10 × 4 mm. 3 .

[0061] Table 3. Test results of combustion, cone calorimetry, and oxygen index of different flame-retardant silicone rubbers.

[0062] As shown in Table 3, the flame-retardant silicone rubbers prepared in Examples 1-6 and Comparative Example 2 exhibit extremely strong flame-retardant properties. In the combustion performance test, it was found that the prepared silicone rubbers did not burn in the flame, did not produce smoke, and all had a flammability rating of V-0. In contrast, the silicone rubbers prepared in Comparative Examples 1 and 3, under the same test conditions, burned violently with a large amount of dense smoke, indicating that the flame-retardant properties of the prepared silicone rubbers were significantly improved.

[0063] Table 3 shows the data on total heat release, total smoke production, total CO release, and peak heat release rate during combustion. It can be seen that the silicone rubbers prepared in Examples 1-6 exhibit significantly reduced total heat release and peak heat release rate during combustion. Although Comparative Example 2 showed better flame retardant performance in the combustion test, its peak heat release rate, total heat release, total smoke production, and total CO production all showed higher test results. Meanwhile, the peak heat release rate, total heat release, total smoke production, and total CO production of Comparative Examples 1 and 3 were all higher than those of Examples 1-6. In the oxygen index test, the LOI value of Comparative Example 1 was 12%, far lower than the LOI values ​​of Examples 1-6. Therefore, the self-healing, in-situ ceramizable fire-retardant silicone rubber of the present invention has excellent flame retardant and smoke generation suppression properties.

[0064] 2: Tensile strength test Tensile strength tests were conducted on the self-healing, in-situ ceramizable, fire-retardant silicone rubber materials prepared in Examples 1-6 and Comparative Examples 1-3. The specific testing procedure is as follows: Tensile strength performance tests were performed on the materials using a universal testing machine. The tensile performance test samples were strip-shaped. After being treated at different temperatures, the samples were tested at a tensile rate of 200 mm / min according to the standard. The experimental results are shown in Table 4.

[0065] Table 4 Tensile strength test results of different flame-retardant silicone rubbers

[0066] Table 4 shows that the tensile strength of the self-healing, in-situ ceramizable fire-retardant silicone rubber materials in Examples 1-6 increased significantly when the temperature increased from 400℃ to 800℃. However, the tensile strength of the samples in Comparative Examples 1-3 decreased with increasing temperature, indicating that controlling the proportions of the self-healing matrix precursor, ceramization precursor, and flame-retardant filler has a significant impact on the mechanical properties of the flame-retardant silicone rubber. Furthermore, compared to Example 2, Example 5 adjusted the position of the reinforcing fiber, resulting in an overall increase in tensile strength; Example 6, based on this, further improved the tensile strength compared to Example 2, which used a single stirring speed, through in-situ reactive stirring in step three.

[0067] 3: Bending strength test The specific testing process is as follows: According to GB / T 9341-2008 "Determination of Bending Properties of Plastics", the bending strength performance test is performed on the material using a universal testing machine. The bending performance test sample is in the shape of a long strip. The test is carried out at a bending rate of 2 mm / min according to the standard. The experimental results of Examples 1-6 and Comparative Examples 1-3 are shown in Table 5.

[0068] Table 5. Flexural strength test results of different flame-retardant silicone rubbers

[0069] Table 5 shows that when the temperature increases from 400℃ to 800℃, the flexural strength of the self-healing in-situ ceramizable fire-retardant silicone rubber materials in Examples 1-6 increases significantly, demonstrating the advantage of the composite ceramic skeleton formed by the synergistic formation of BO-Si and BO-Al chemical bonds by the boron element in the self-healing dynamic covalent network and the silicon and aluminum elements in the ceramization precursor. In contrast, the tensile strength of the samples in Comparative Examples 1-3 decreases with increasing temperature, indicating that controlling the proportions of the self-healing matrix precursor, ceramization precursor, and flame-retardant filler has a significant impact on the mechanical properties of the flame-retardant silicone rubber. Similar to the tensile strength, Example 5, compared to Example 2, shows an increase in overall flexural strength due to the adjustment of the reinforcing fiber addition position; Example 6, based on this, further improves the flexural strength compared to Example 2, which uses a single stirring speed, through in-situ reactive stirring in step three. Example 4, which does not use reinforcing fibers, shows a more significant decrease in flexural strength compared to Example 2.

[0070] 4: Self-healing performance test The prepared silicone rubber material was punched or cut into standard dumbbell-shaped specimens using a cutter. Using a universal testing machine, under standard laboratory temperature (23±2℃), a tensile test was performed on the original specimens at a fixed tensile speed (200 mm / min) until fracture. The maximum tensile stress a1 at fracture of each specimen was recorded. The healed silicone rubber material was then subjected to a tensile test again, and the maximum tensile stress a2 at fracture of each specimen was recorded again. The self-healing efficiency was obtained as a2 / a1.

[0071] Depend on Figure 1 It can be seen that Examples 1-6 all exhibit good self-healing efficiency (all above 78%), with Examples 2, 5, and 6 showing self-healing efficiencies above 92%. In contrast, Comparative Examples 2-3 only demonstrate self-healing efficiencies of 60% and 42%, respectively, while Comparative Example 1, a commercially available silicone rubber, does not exhibit self-healing properties. Therefore, the prepared self-healing in-situ ceramizable fire-retardant silicone rubber material possesses excellent self-healing performance.

[0072] 5: Morphology test of carbon slag after cone measurement The residues from Examples 1-6 and Comparative Examples 1-3 after cone tapping were subjected to SEM testing. Figure 2 As shown, Comparative Example 1 (corresponding to) Figure 2 (a) Comparative Example 2 (corresponding to) Figure 2 (b) Comparative Example 3 (corresponding to) Figure 2 Samples in (c) all exhibited large cracks. In contrast, such as Figure 3 As shown, Example 1 (corresponding to) Figure 3 (a) Example 2 (corresponding) Figure 3 (b) Example 3 (corresponding) Figure 3 (c) The prepared sample maintained its structure at high temperature, forming a dense and smooth char layer, further demonstrating the excellent flame-retardant properties of the prepared silicone rubber. The SEM images of the samples prepared in Examples 4-6 are basically consistent with those in Example 2, and can be referred to accordingly. Figure 3 (c).

[0073] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention. Clearly, those skilled in the art can make various alterations and modifications to the invention without departing from its spirit and scope. Thus, if these modifications and modifications of the invention fall within the scope of the claims and their equivalents, the invention is also intended to include these modifications and modifications.

Claims

1. A method for preparing a self-healing in-situ ceramicized flame-retardant silicone rubber, characterized in that, Includes the following steps: Step 1: Mix terminal hydroxyl siloxane and boron ester crosslinking agent at low speed at room temperature to obtain a self-healing matrix precursor with dynamic covalent network. Step 2: After vacuum drying the ceramicized precursor and flame-retardant filler, add the self-healing matrix precursor in sequence and accelerate stirring to mix evenly. Step 3: Add catalyst and mix evenly, then pour into mold and cure at room temperature to obtain the self-healing in-situ ceramicized flame-retardant silicone rubber; The ceramicized precursor includes a premixed silicon-containing component, low-temperature glass powder, and metal oxides. The silicon-containing component includes one or more of nano-silica, silica powder, and silica sol. The softening point of the low-temperature glass powder is between 400 ℃ and 600 ℃, and includes one or more of borosilicate glass powder and phosphate glass powder; The metal oxide includes one or more of kaolin, mica powder, aluminum hydroxide, and aluminum oxide.

2. The preparation method according to claim 1, characterized in that, Hydroxyl-terminated siloxanes include α,ω-dihydroxy polydimethylsiloxane, whose number-average molecular weight Mn is 10,000-100,000; Borate ester crosslinking agents include one or more of triethyl borate, tri-n-propyl borate, triisopropyl borate, and bisphenol A borate. The catalysts include silane coupling agents and dibutyltin dilaurate.

3. The preparation method according to claim 1, characterized in that, The ceramicization precursor includes a premixed silicon-containing component, low-temperature glass powder, and metal oxides; Flame-retardant fillers include premixed inorganic hydroxides, expandable carbon sources, and carbonization catalysts; In step two, the ceramicized precursor and flame-retardant filler are vacuum dried in a vacuum oven at 60-80℃ for 10-15 hours.

4. The preparation method according to any one of claims 1-3, characterized in that, The preparation method further includes adding reinforcing fibers in at least one of (1) and (2): (1) In step two, the reinforcing fiber pretreatment is added to the self-healing matrix precursor after the flame retardant filler is added; (2) In step one, the reinforcing fiber is pretreated, premixed with terminal hydroxyl siloxane, and then mixed with a boron ester crosslinking agent so that the reinforcing fiber is pre-embedded in the dynamic covalent network; The pretreatment of the reinforcing fibers includes: Keep the reinforcing fibers at 350-400℃ for 30-60 minutes; The reinforcing fibers are surface activated using plasma or corona treatment.

5. The preparation method according to any one of claims 1-3, characterized in that, In step one, stir at the first stirring speed of 20-50 rpm for 8-15 minutes; In step two, stir at the second stirring speed of 100-200 rpm for 45-75 minutes; In step three, in-situ reactive stirring is carried out at a gradually decreasing third stirring speed, including the following steps: V1 is 120-150 rpm, stirring for 1-3 min, to rapidly and uniformly disperse the catalyst in a low-viscosity system under high-speed shear; V2 is 80-110 rpm, stirring for 1-3 minutes. Under medium-speed shear, the materials are fully in contact and reacted. The heat generated by stirring and shear is controlled to keep the system temperature below 35℃. V3 is stirred at 40-70 rpm for 0.5-2 min to allow air bubbles to escape from the system under low-speed shearing and to prevent excessive cross-linking.

6. A self-healing in-situ ceramicized flame-retardant silicone rubber prepared by the preparation method according to any one of claims 1-5, characterized in that, By weight, its raw material composition includes: Adjust the amount of self-healing matrix precursor to 25-55 parts; 25-40 parts of ceramization precursor; 20-35 parts of flame-retardant filler; Catalyst 1.0-2.5 parts; In the self-healing matrix precursor, the mass ratio of terminal hydroxyl siloxane to boron ester crosslinking agent is (5-15):1; The ceramic precursor comprises a silicon component provider, low-temperature glass powder, and metal oxide in a mass ratio of (3-6):(4-8):(2-5).

7. The self-healing in-situ ceramicized flame-retardant silicone rubber as described in claim 6, characterized in that, The flame-retardant filler comprises an inorganic hydroxide, an expandable carbon source, and a carbonization catalyst in a mass ratio of (4-8):(1-3):(1-3); The catalyst comprises a silane coupling agent and dibutyltin dilaurate in a mass ratio of (5-12):(4-8).

8. The self-healing in-situ ceramicized flame-retardant silicone rubber as described in claim 7, characterized in that, In the flame-retardant filler, the inorganic hydroxide is one or a combination of two of aluminum hydroxide and magnesium hydroxide, and the surface of the inorganic hydroxide is hydrophobically modified by silane coupling agent or hexamethyldisilazane. The expandable carbon source is one or a combination of two of expanded graphite and expandable graphite, and the surface of the expandable carbon source is grafted and modified with a silane coupling agent. The char-forming catalyst is one or more of ammonium polyphosphate, melamine phosphate, and pentaerythritol phosphate.

9. The self-healing in-situ ceramicized flame-retardant silicone rubber as described in claim 6, characterized in that, It also includes 2.5-5.0 parts of reinforcing fiber, which is chopped fiber with a length of 1-6 mm and a diameter of 5-20 μm, selected from one or more of basalt fiber, glass fiber, and aluminosilicate ceramic fiber.

10. The self-healing in-situ ceramicized flame-retardant silicone rubber according to any one of claims 6-9, characterized in that, The self-healing in-situ ceramicized flame-retardant silicone rubber has a tensile strength of over 18 MPa and a flexural strength of over 15 MPa, and its tensile strength and flexural strength gradually increase from 400℃ to 800℃.

Citation Information

Patent Citations

  • Fire-resistant silicone rubber self-adhesive tape and its preparation method

    CN103613934B

  • A ceramicizable silicone rubber composite, ceramicizable silicone rubber, its preparation method and applications

    CN115537137B